An innovative approach to stormwater management accounting for spatial variability in soil permeability - Kannangara, Dumal; Sarukkalige, Priyantha Ranjan; Botte, M. (Engineers Australia, 2012)
In the past few years, major flooding incidents have been experienced in Australia. This has resulted in increased concerns for local authorities, environmental institutions and the public, giving management of stormwater a new priority. Stormwater infiltration is one of the best practise methods to operationally and sustainably handle urban drainage. However, until recently, stormwater management strategies have failed to adequately consider the criticality of spatially varying soil permeability and their implications on drainage designs. With a lack of detailed information on local soil properties, it is difficult to assess the adequacy of stormwater retention / detention requirements. This study was carried out in new land development areas of Gosnells in Western Australia, focusing on identification of soil properties and development of a typology of suitable stormwater management strategies with respect to applicable infiltration capacities. The Guelph Permeameter and the falling head methods were used to investigate the in-situ and laboratory saturated hydraulic conductivities. Test results were categorized into four permeability groups; very rapid (> 1.56 m/day), rapid (0.48<1.56 m/day), moderate (0.12<0.48 m/day) and slow (<0.12 m/day). Finally, these four key permeability categories, combined with the scale of application (lot, street, regional) and operational objective (quality, quantity, conservation), enabled the identification of suitable stormwater management approaches. The results of this study will assist land developers, engineering consultants and local authorities to devise locally appropriate, functional and water sensitive drainage approaches.